2008
DOI: 10.3122/jabfm.2008.05.070266
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Racial/Ethnic Differences in Colorectal Cancer Screening

Abstract: Introduction: Racial/ethnic differences in colorectal cancer (CRC) screening rates are thought to account, in part, for the racial/ethnic differences in CRC disease burden. The purpose of this study was to examine which factors mediate racial/ethnic differences in CRC screening.Methods: Five hundred sixty participants attending a primary care clinic, aged 50 to 80 years, and of African-American, Hispanic, or non-Hispanic white race/ethnicity were interviewed. The goal was to assess the contribution of sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
66
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 64 publications
14
66
5
Order By: Relevance
“…This gap is smaller in magnitude than most prior studies, which have documented Black/White differences in CRCS ranging from 6% to 18%, 14,16,18,19,[65][66][67] but is consistent with more recent results from national surveys and a prior VA study that used a nationally representative sample. 68 In addition, this observed disparity was no longer present when we adjusted for demographic and health factors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This gap is smaller in magnitude than most prior studies, which have documented Black/White differences in CRCS ranging from 6% to 18%, 14,16,18,19,[65][66][67] but is consistent with more recent results from national surveys and a prior VA study that used a nationally representative sample. 68 In addition, this observed disparity was no longer present when we adjusted for demographic and health factors.…”
Section: Discussionsupporting
confidence: 86%
“…[21][22][23][24] This study builds upon prior studies examining racial disparities in adherence to CRCS, only a few of which have examined the extent to which cognitive and environmental factors contribute to disparities. 19,66 Counter to our hypotheses, race differences in adherence to CRCS were explained by race differences in demographic/health-related factors and social/medical environmental factors, but not by cognitive factors. Although more research is needed to fully understand this pattern of results, it is likely that race differences in utilization of the VA as a source of care is a contributing factor.…”
Section: Discussionmentioning
confidence: 65%
“…[1][2][3][4] However, its effectiveness for reducing CRC mortality for vulnerable populations is unclear, given the barriers to colonoscopy, including cost, transportation problems, preparing for the procedure, and fear of invasive tests. [5][6][7][8][9][10][11][12] Expanded use of FOBT, a modality with fewer barriers, may be a viable approach to address CRC screening disparities, especially with single-sample fecal immunochemical tests (FIT), which do not require dietary restrictions. 13 Several randomized trials have reported that outreach with FOBT can improve CRC screening rates.…”
Section: Introductionmentioning
confidence: 99%
“…1 There is limited information on the role of CRC knowledge and other factors that influence willingness to be screened in age appropriate diverse women. Most persons respond that their physician's recommendation is essential to obtain a screening test, 2,3 and facilitating access to health care and screening tests becomes a dominant factor. However, individual factors such as age, knowledge of risks and benefits of screening, belief in following screening guidelines and risk perception may also affect intent to screen.…”
Section: Introductionmentioning
confidence: 99%
“…However, individual factors such as age, knowledge of risks and benefits of screening, belief in following screening guidelines and risk perception may also affect intent to screen. 2,4 Finally, since screening benefits in terms of mortality reduction are measured at the population level, most women who are screened do not receive individual benefit other than the knowledge of being disease free. Our goal was to understand the factors associated with willingness to undergo and continue CRC screening, and to ask whether or not women are willing to have CRC screening with the accompanying personal risk to achieve a public health benefit of decreasing population cases.…”
Section: Introductionmentioning
confidence: 99%